2006
DOI: 10.1038/sj.emboj.7601313
|View full text |Cite
|
Sign up to set email alerts
|

A homologue of the breast cancer-associated gene BARD1 is involved in DNA repair in plants

Abstract: hBRCA1 and hBARD1 are tumor suppressor proteins that are involved as heterodimer via ubiquitinylation in many cellular processes, such as DNA repair. Loss of BRCA1 or BARD1 results in early embryonic lethality and chromosomal instability. The Arabidopsis genome carries a BRCA1 homologue, and we were able to identify a BARD1 homologue. AtBRCA1 and the putative AtBARD1 protein are able to interact with each other as indicated by in vitro and in planta experiments. We have identified T-DNA insertion mutants for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 62 publications
3
72
0
Order By: Relevance
“…A mutation in the BRCA1-associated RING domain1 gene caused both a defect in DNA repair and in the maintenance of SAM organization by repressing WUS expression in plants (Reidt et al, 2006;Han et al, 2008). In a previous study, double-knockdown lines of the cyclin-dependent kinases CDKB2;1 and CDKB2;2 showed abnormal SAMs and phyllotaxis, suggesting a close link between cell cycle progression and the regulation of meristem organization in plants (Andersen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A mutation in the BRCA1-associated RING domain1 gene caused both a defect in DNA repair and in the maintenance of SAM organization by repressing WUS expression in plants (Reidt et al, 2006;Han et al, 2008). In a previous study, double-knockdown lines of the cyclin-dependent kinases CDKB2;1 and CDKB2;2 showed abnormal SAMs and phyllotaxis, suggesting a close link between cell cycle progression and the regulation of meristem organization in plants (Andersen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…involved in HR or its regulation (e.g. bard1, rad51C, and rad54) are also sensitive to cross-linking agents (Abe et al, 2005;Osakabe et al, 2006;Reidt et al, 2006;Shaked et al, 2006). Moreover, they are deficient in intrachromosomal HR, but in contrast to rad5a not only after bleomycin treatment but also without DSB induction.…”
Section: Atrad5 Is Involved In Dsb-induced Hr In Somatic Cellsmentioning
confidence: 99%
“…BRCA1 and BRCA2 orthologs appear to be present in all vertebrate genomes. A BRCA2 homolog has been identified in the fungus Ustilago maydis [20] and homologs of BRCA1 exist in worms and in some plant species [21][22][23][24], but both genes appear to be absent from the genomes of Saccharomyces cerevisiae and Schizosaccharomyces pombe. The reason for this patchy representation of BRCA genes across evolution is not well understood.…”
Section: Introductionmentioning
confidence: 99%